Therapeutic targeting of tumor‐associated macrophages in pancreatic neuroendocrine tumors. Issue 7 (3rd September 2018) - Krug, Sebastian; Abbassi, Rami; Griesmann, Heidi; Sipos, Bence; Wiese, Dominik; Rexin, Peter; Blank, Annika; Perren, Aurel; Haybaeck, Johannes; Hüttelmaier, Stefan; Rinke, Anja; Gress, Thomas M.; et al.
Abstract : Pancreatic neuroendocrine tumors (PNETs) represent a heterogeneous group of neuroendocrine neoplasms with varying biological behavior and response to treatment. Although targeted therapies have been shown to improve the survival for patients at advanced stage, resistance to current therapies frequently occurs during the course of therapy. Previous reports indicate that the infiltration of tumor‐associated macrophages (TAMs) in PNETs might correlate with tumor progression and metastasis formation. We aimed to evaluate the prognostic and functional impact of TAMs in human PNETs in vitro and in vivo and to investigate the effect of therapeutic targeting TAMs in a genetic PNET mouse model. TAM expression pattern was assessed immunohistochemically in human PNET tissue sections and a tissue‐micro‐array of PNET tumors with different functionality, stage, and grading. The effect of liposomal clodronate on TAM cell viability was analyzed in myeloid cell lines and isolated murine bone macrophages (mBMM). In vivo, RIP1Tag2 mice developing insulinomas were treated with liposomal clodronate or PBS‐Liposomes. Tumor progression, angiogenesis and immune cell infiltration were assessed by immunohistochemistry. In human, insulinomas TAM density was correlated with invasiveness and malignant behavior. Moreover, TAM infiltration in liver metastases was significantly increased compared to primary tumors. In vitro, Liposomal clodronate selectively inhibited the viability of myeloid cells and murine bone macrophages, leaving PNET tumor cell lines largely unaffected. In vivo, repeated application of liposomal clodronate to RIP1Tag2 mice significantly diminished the malignant transformation of insulinomas, which was accompanied by a reduced infiltration of F4/80‐positive TAM cells and simultaneously by a decreased microvessel density, suggesting a pronounced effect of clodronate‐induced myeloid depletion on tumor angiogenesis. Concomitant treatment with the antiangiogenic TKI sunitinib, however, did not show any synergistic effects with liposomal clodronate. TAMs are crucial for malignant transformation in human PNET and correlate with metastatic behavior. Pharmacological targeting of TAMs via liposomal clodronate disrupts tumor progression in the RIP1Tag2 neuroendocrine tumor model and was associated with reduced tumor angiogenesis. Based on these results, using liposomal clodronate to target proangiogenic myeloid cells could be employed as novel therapeutic avenue in highly angiogenic tumors such as PNET. Abstract : What's new? Tumor‐associated macrophages, or TAMs, are an important component of the tumor microenvironment. These cells seem to promote tumor growth and thwart the cytotoxic effect of cancer therapy. Here, the authors investigated how the presence of TAMs affects the progression of pancreatic neuroendocrine tumors (PNETs). Using tissue samples from a variety of PNETs, they observed that more infiltrating TAMs correlate with increased angiogenesis, proliferation and metastasis. In a mouse model, treatment with liposomal clodronate depleted TAMs, which decreased angiogenesis and reduced tumorigenesis and progression. Combining clodronate with established antiangiogenic treatment provided no additional benefit, however.